The Meaning of Death in the Poem Tuan dan Pada Sebuah Maghrib by Supardi Djoko Damono: A Theological Analysis Based on Surah Ali-Imran verse 185 in Ibn Kathir's Tafsir - Izzatul Ishlah Alfatih; Muhammad Iqbal Maulana; Syarifudin Yunus (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study uses a qualitative descriptive research method, namely providing an overview of the meaning of death in the poems